Catalytic asymmetric borylative aldol reaction of 5, 6-dihydro-2H-pyran-2-one and ketones. Issue 12 (22nd March 2019) - Zhang, Qi; Jia, Xueshun; Yin, Liang
Abstract: A copper(I)-catalyzed asymmetric borylative aldol reaction of 5, 6-dihydro-2 H -pyran-2-one and simple ketones (including aromatic ketones and an aliphatic ketone) was disclosed, which afforded a series of chiral diols after an oxidative work-up in moderate yields with moderate to high diastereoselectivity and excellent enantioselectivity. The lactone moiety was easily opened with methanol to generate a chiral triol in moderate yield. Graphical abstract: Image 1